The Professional Development of a Facilitator through a Study Group (2007)
ABSTRACT: This article presents part of the results of a study that was conducted to observe the professional development of a group of foreign language teacher educators and preservice teachers. The study focused on the knowledge, skills and attitudes these teachers developed through their participation in a study group. This article reports specifically on the skills and attitudes the facilitator of the study group developed due to her role in it.